Tuning the distribution of Tb in Nd-Fe-B sintered magnet to overcome the magnetic properties trade-off. (August 2022) - Wang, Zhanjia; Yue, Ming; Liu, Weiqiang; Li, Yuqing; Wu, Haihui; Liu, Youhao; Zha, Shanshun; Yi, Xiaofei; Zhang, Dongtao; Lu, Qingmei; Zhang, Hongguo
Abstract: A trade-off between the coercivity and other magnetic properties (remanence and maximum energy product) is a dilemma in current grain boundary diffusion (GBD) Nd-Fe-B sintered magnets. Here we report a new solid-liquid phase separation diffusion method for Nd-Fe-B magnets, which substantially and comprehensively enhances permanent magnetic performance, especially demagnetization curve squareness. The results show Tb diffused preferentially into the inside of magnets through the molten Nd-rich grain boundary phase during the liquid phase diffusion process. Then, uniform core-shell structures were formed during the subsequent solid phase diffusion process. This new GBD strategy increases the diffusion depth and avoids the evident Tb gradient that cause the deterioration of the magnetic performance of current GBD magnets. The microstructure and magnetic domain evolution in the Nd-Fe-B magnets diffused with both current and newly-developed techniques were also compared and investigated. Graphical abstract: Image, graphical abstract